ANALISIS DISPENSASI PERKAWINAN TERHADAP JUMLAH PERNIKAHAN DINI DAN PERCERAIAN - Putri Chusnul Nur Iman Safitri (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2025)
Marriage dispensation is a legal mechanism that allows for exceptions to the minimum age of marriage under certain conditions. This study examines the granting of marriage dispensations at the Jombang Religious Court and their relationship with early marriage and divorce patterns. A juridical-empirical method was applied, including analysis of court administrative data, interviews with judges, and literature review. The findings indicate that, although the number of dispensation requests has declined, the predominant reason remains pregnancy outside of marriage, alongside economic, educational, and cultural factors. Granting these dispensations has significant implications, including increased vulnerability of young couples to school dropout, reproductive health issues, and economic burdens on families. From a legal perspective, the findings highlight a gap between the objectives of Law No. 16/2019 and its implementation in practice. These results provide important insights for policymakers, legal practitioners, and social institutions aiming to reduce child marriage and its adverse consequences.